The Effect of Learning the National Song with the Drill Method to Determine Students' Cognitive Learning Outcomes in Cultural Arts Subjects in Grade VI Elementary School: Pengaruh Pembelajaran Lagu Nasional Dengan Metode Drill Untuk Mengetahui Hasil Belajar Kognitif Siswa Dalam Mata Pelajaran Seni Budaya di Kelas Vi SD - Murviara Balqis; Evie Destiana (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe the effect of the Drill Method on Knowing Student Cognitive Learning Outcomes in Cultural Arts Subjects in Class VI Sd Negeri Pilang - Sidoarjo and describe the effect of the Drill Method on Knowing Student Cognitive Learning Outcomes in Cultural Arts Subjects in Class VI Public Elementary School Pilang - Sidoarjo. This type of research uses a quantitative research approach. This study used the One Group Pretest Posttest design. The population used in this study were all students in class VI SD Negeri Pilang - Sidoarjo with a sample of 28 students. Data collection techniques in this study used learning outcomes tests, where there are pretest (initial test) and postest (final test). The data obtained were then calculated using the t-test and the values ​​obtained were T count = 1.096 T table = 11.070 with a significant level of 5% and dk 28. The t value was outside the acceptance of Ho, so Ho was rejected and Ha was accepted. Based on the results of the study, it can be concluded that the effect of learning the national song with the drill method to determine the cognitive learning outcomes of students in cultural arts subjects in class VI SD Negeri Pilang - Sidoarjo has a major effect on student cognitive learning outcomes in cultural arts subjects in class VI - public elementary schools. pilang - Sidoarjo.